Corruption undermines Malaysia's stability: contrastingly charity fosters societal cohesion and national integrity - Irma Wani Othman; Nur Hidayah Iwani Mohd Kamal; Muhammad Safuan Yusoff; Saifulazry Mokhtar (Global Academic Excellence, 2024)
This paper examines corruption across various contemporary issues, highlighting its role in destabilizing Malaysia as a nation and drawing a comparative analysis with the practice of charity. This analysis seeks to broaden societal perspectives and promote charitable acts, ultimately deterring criminal behavior through a deeper understanding of its religious implications. A qualitative research approach, based on positivist philosophy, is employed to investigate corruption as a cultural phenomenon. This method combines data from various sources to allow for an inductive or qualitative data analysis, with a focus on deriving general meanings. The study relies on qualitative academic journal research, offering descriptive analytical discussions as a primary source, including a range of scholarly journal articles. Additionally, published data and articles from official government and non-government websites provide relevant information on corruption issues. The findings of this study reveal that corruption and charity are ideologically distinct, especially from legal and Islamic perspectives. This discussion explores the extent to which corruption is understood as a criminal offense violating legal norms within Malaysian society.